South Africa : Financial Sector Assessment Program-Technical Note on Banking Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2022)
The implementation of a twin peaks model represents a significant change to the South African financial supervisory architecture. The Prudential Authority (PA), operating within the administration of the South African Reserve Bank (SARB), is responsible for promoting and enhancing the safety and soundness of financial institutions that provide financial products and securities services. A separate authority, the Financial Sector Conduct Authority2 (FSCA), is responsible for market conduct regulation and supervision. The introduction of the twin peaks architecture was motivated by a need to increase the robustness of the financial sector regulatory and supervisory system, reinforce financial stability, improve protection of customers, and enhance cooperation among the regulators.